Antecedent model of happiness in UAE - Alsuwaidi, Essa Yousuf Majid (2022)
Working is one of the most essential aspects of the majority of individuals, it empowers them and give them chance in bettering their lives. However, with the increased competition in workplace, organizations are relentlessly trying to optimize the best output and performance they can gain from their employees. A shift in focus to happiness at workplace is becoming norm, as organizations that adopts this approach believes that a satisfied employee is a productive employee. To avoid the losses from turnovers, companies are trying their best to retain their workers as to avoid losing the number of resources they have invest into the staffing training and working experience. Nonetheless, with all the discussions regarding happiness at workplace that is happening all around the globe, the UAE have been left behind. There are limited number of discourses and studies that have been carried out around the UAE regarding workers’ happiness. This research aims to identify the antecedent of employee happiness in UAE public sector. Based on the transformational leadership (TL) theory, psychological contract theory, broaden and built, and affective events, this study proposed that the effect of TL on employee happiness, organizational culture, employee satisfaction, and employee empowerment is positive. The study also proposed that the effect organizational culture and empowerment on employee satisfaction and employee happiness are positive. Further, employee empowerment and employee satisfaction. The population of this study are the public organization in UAE. A questionnaire survey using 5-points Likert scale to gauge the respondents of this study regarding their perspective on workplace happiness was used as an instrument of data collection. From the targeted 370 samples for this study, 260 usable questionnaire feedback was actually received. Univariate analysis and multivariate analysis have been carried out using SPSS and AMOS as embedded in structural equation modeling. The findings showed that TL has an insignificant effect on employee happiness, but it has a significant effect on organizational culture, employee satisfaction, and employee empowerment. Organizational culture and empowerment have significant effect on employee satisfaction and employee happiness. In addition, employee satisfaction affected employee happiness. Organizational culture and employee empowerment mediated the effect of TL on employee happiness. Further, employee satisfaction mediated the effect of organizational culture and employee empowerment on employee happiness. Decision makers in UAE are recommended to utilize the findings of this study to enhance the happiness among employees in public organizations.